Between privilege and burden: Work past retirement age in Germany and the UK - Simone Scherger; Steffen Hagemann; Anna Hokema; Thomas Lux (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2012)
The paper investigates paid work beyond retirement age in Germany and the UK. This comprises a combination of work, payments from a pension (or several pensions) and old age which is counter to the assumed finality of retirement and the corresponding standardised passage from end of work into retirement and receipt of a pension. Paid work beyond retirement has not only become more frequent in the last decade, but is also part of heated policy debates on pension reform. The paper first gives a comprehensive literature review, presenting empirical results, conceptual differentiations and theoretical approaches to post-retirement work from previous studies. A heuristic model summarises the most important individual and structural influences on post-retirement work. Thereafter, the most important features of the pension systems and labour markets in Germany and in the UK are outlined. In terms of institutional settings, the countries represent opposing cases whose comparison helps to better understand the institutional factors shaping employment beyond retirement age. In the second half of the paper, data from the German Ageing Survey (DEAS) and the English Longitudinal Study of Ageing (ELSA) serve to empirically describe paid work beyond retirement age. In addition to the demographic and regional distribution of postretirement work, particular attention is paid to the socio-economic status of people working past retirement, in comparison to those who do not work. Other important areas studied are non-paid activities of post-retirement workers, their health and living arrangements as well as their life satisfaction and subjective reasons for employment. On the one hand, the results of the empirical description confirm the privileged situation of many post-retirement workers who, for example, tend to be more highly educated and have better health than their non-working counterparts. On the other hand, some post-retirement workers work for financial reasons and in the low-paid service sector. There are some indications that the latter group, who experience post-retirement work more often as a burden, or at least in a more ambivalent way, is larger in the UK than in Germany, mainly for institutional and structural reasons. – – Dieses Arbeitspapier beschäftigt sich mit Erwerbsarbeit jenseits der Rentengrenze in Deutschland und Großbritannien. Mit Erwerbsarbeit jenseits der Rentengrenze ist eine Kombination von bezahlter Arbeit, Rentenzahlungen und Alter gemeint, die im Kontrast steht zur Endgültigkeit des Ruhestands und dem entsprechenden standardisierten Übergang aus der Erwerbsarbeit in den Ruhestand und zum Empfang von Rentenzahlungen. Erwerbsarbeit jenseits der Rentengrenze ist in den letzten zehn Jahren nicht nur häufiger geworden; sie wird auch intensiv debattiert, etwa im Rahmen von Diskussionen zu Rentenreformen. Das Arbeitspapier gibt zunächst einen umfassenden Literaturüberblick, der bisherige empirische Ergebnisse, konzeptuelle Differenzierungen und theoretische Annäherungen an Erwerbsarbeit jenseits der Rentengrenze einschließt. Ein heuristisches Modell fasst die wichtigsten individuellen und strukturellen Einflüsse auf Arbeit jenseits der Rentengrenze zusammen. Anschließend werden sowohl die Rentensysteme als auch die Arbeitsmarktstrukturen Deutschlands und Großbritanniens in groben Zügen beschrieben. Was den institutionellen Rahmen angeht, repräsentieren die beiden Länder zwei gegensätzliche Fälle, deren Vergleich dazu beiträgt, die institutionellen Faktoren zu verstehen, welche Erwerbsarbeit jenseits der Rentengrenze prägen. In der zweiten Hälfte des Arbeitspapiers werden Daten des Deutschen Alters-Surveys (DEAS) und der English Longitudinal Study of Ageing dazu genutzt, Erwerbsarbeit jenseits der Rentengrenze empirisch zu beschreiben. Über die soziodemographischen Charakteristika von erwerbstätigen Rentnern und die regionale Verteilung dieser Form von Arbeit hinaus wird dem sozio-ökonomischem Status erwerbstätiger Rentner im Vergleich zu anderen Rentnern besondere Aufmerksamkeit gewidmet. Außerdem werden unbezahlte Aktivitäten erwerbstätiger Rentner, ihre Gesundheit und Lebensformen sowie ihre Lebenszufriedenheit und die subjektiven Gründe für ihre Arbeit beschrieben. Einerseits bestätigen die Ergebnisse der Beschreibung die eher privilegierte Situation erwerbstätiger Rentner, die beispielsweise eine bessere Bildung aufweisen und gesünder sind als nicht-erwerbstätige Rentner. Andererseits gibt es erwerbstätige Rentner, die aus finanziellen Gründen und im schlechtbezahlten Dienstleistungssektor arbeiten. Einiges deutet darauf hin, dass die letztgenannte Gruppe, die ihre Arbeit häufiger als eine Bürde oder zumindest ambivalent erlebt, in Großbritannien größer ist als in Deutschland, und zwar vor allem aus institutionellen und strukturellen Gründen.
Keywords: 300